Development of Semut Island Ecotourism in Limbungan Village, Pekanbaru City: Pentahelix Model Approach - Fatmawati, Fatmawati; Andriani, Roza (Indonesian Journal of Tourism and Leisure, 2024)
The tourism sector plays a vital role in enhancing the economic growth of a community. Effective tourism development requires collaboration not only from the government but also among academics, businesses, local communities, and the media. Such collaboration fosters public awareness of the importance of tourism and helps optimize existing tourism potential. Pekanbaru City, for example, possesses significant tourism development opportunities rooted in local culture, one of which is Semut Island. However, local communities face challenges in developing ecotourism, which can hinder their economic activities. This study addresses the urgent need to explore these obstacles. The aim of this research is to analyze the collaboration among the various stakeholders in the pentahelix model as they work towards developing ecotourism at Semut Island in Limbungan Village, Pekanbaru City. This study employs qualitative methods and involves stakeholders from academia, business, local communities, government, and the media as informants. Data is collected using purposive sampling, a technique that helps researchers select informants who are relevant to the study's theme. The findings indicate that collaboration among stakeholders in the pentahelix model is functioning effectively, with each group fulfilling its respective role in developing Semut Island's ecotourism. However, there is a need for improved collaboration and coordination among these actors to ensure the ongoing success of Semut Island ecotourism and to effectively stimulate the economic growth of the local community.